The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/mop.28830
|View full text |Cite
|
Sign up to set email alerts
|

Compact frequency selective surface with dual band response for WLAN applications

Abstract: In this article, the authors propose the use of conducting patches with slots to design frequency selective surfaces (FSS) with dual bandstop for wireless LAN (WLAN) applications. The simulated results were obtained with the computer program Ansoft Designer TM . A prototype of the designed FSS was built and its transmission characteristics were measured. Excellent agreement between simulated and measured results was obtained. The FSS was useful for rejecting signals from industrial, scientific, and medical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…2 Hence, research to improve the spectrum efficiency in indoor environments by using a frequency selective shielding (FSS) wall structure that either passes or reduces a specific frequency band is needed. 3,[8][9][10] Furthermore, an active research effort has been ongoing on spectrum efficiency control through the application of an active FSS (AFSS) wall structure in a building that can actively change the passing or reducing frequencies. Widely known areas of application that utilizes this electromagnetic property include radome in fighter jets and electromagnetic wave absorbent material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Hence, research to improve the spectrum efficiency in indoor environments by using a frequency selective shielding (FSS) wall structure that either passes or reduces a specific frequency band is needed. 3,[8][9][10] Furthermore, an active research effort has been ongoing on spectrum efficiency control through the application of an active FSS (AFSS) wall structure in a building that can actively change the passing or reducing frequencies. Widely known areas of application that utilizes this electromagnetic property include radome in fighter jets and electromagnetic wave absorbent material.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[7][8][9][10][11][12][13][14] In recent years, research has been conducted to evaluate the signal performance indirectly by simulating the received signal strength, delay spread, and channel capacity to check whether the indoor wireless LAN communication performance can be improved. 3,4,[7][8][9][10][11][12][13][14] In recent years, research has been conducted to evaluate the signal performance indirectly by simulating the received signal strength, delay spread, and channel capacity to check whether the indoor wireless LAN communication performance can be improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dual band FSS is built by cascading a metal loop shaped layer and its complementary in . Cascading two layers of conducting patches with slots to design dual bandstop FSS is used in . Left‐handed structures and capacitive grids are used to design dual band FSS in .…”
Section: Introductionmentioning
confidence: 99%
“…In [9], the authors enhance their previous work and study the stability for both TE and TM polarized waves not only for normal incident wave but also for oblique incidence angles. In [10], the authors showed a project of cascading FSS to block the second and third ISM bands and UNII band. In [11], the authors proposed a compact FSS to reject 5 GHz band with angular stability for TE and TM modes of polarization.…”
mentioning
confidence: 99%